Investigating the causes of occupational diseases among fishermen - Eka Muftiana Rahmawati; Anderias Umbu Roga; Luh Putu Ruliati; Jefri Bale; Noorce Christiani Berek (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The informal sector, characterized by its lack of structure, formality, and legal recognition, often receives inadequate attention regarding occupational health. In Indonesia, over 60% of the population resides in coastal areas, with the majority working as fishermen. Due to the inherently high-risk nature of fishing at sea, fishermen are frequently exposed to unpredictable ocean conditions, making them susceptible to various work-related health issues, including musculoskeletal disorders, dermatitis, keratopathy, and barotrauma. Purpose: To investigate the factors linked to the occurrence of occupational diseases among fishermen. Method: A descriptive correlational, specially focusing on cross-sectional method. The study took place in December 2024 in Kupang City. The independent variable was knowledge, duration of work, unsafe behaviors, and unsafe working conditions. The dependent variable included the incidence of occupational diseases. Using random sampling and Lameshow formula 89 respondents were selected who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using chi-square test. Results: The study found significant associations between length of work and occupational diseases (p = 0.011), and between behavior and occupational diseases (p = 0.001), while knowledge and environmental conditions showed no significant effects. Conclusion: Occupational diseases result from multifactorial determinants, including exposure duration, behavior, and environmental conditions. For informal workers such as fishermen, government involvement in risk management and safety governance is essential. Preventive measures should focus on skill development, occupational safety culture, proper use of protective equipment, health education, and access to health insurance.